Health care practices of AMCHIS in the himalayan communities of Nepal: A study in upper-dolpa. - Pahadi, Toya Nath (2006)
ABSTRACT: Although Amchis have been providing basic health care to the high Himalayan marginalized boarder communities of Nepal from the time immemorial, very few know about them regarding their medical practices and professional status out side the region. Despite their valuable contribution to meet local health care needs form generations. Government has neither recognized nor supported to them and their medical practices till now. Amchis and their health care practices have been in shadow due to lack for adequate research attempts. Despite its high utilization and excessive contribution to meet local health care needs, less priority has been given for research in such traditional medicine sector. In this context, the investigator had attempted to study on "Health Care Practices of Amchis in the Himalayan Communities of Nepal." The main objectives of this study were identify the pattern of health care practices of Amchis, to analyze the contributing factors for utilization of their health care practices, to identify people's attitude towards their health care practices, to find out their professional status and to identify the problems and challenges for conservations of this health care practice and their measures for solution. This study was carried out in the seven VDCs of Upper-Dolpa utilizing descriptive research design. 10% (125) heads HH, 14 key information Amchis , and 10% (103) patients treated by Amchis in the last year were selected. Random sampling was adopted to select the head of households and to select the patients treated by Amchis , while purposive sampling was adopted to select the key informant Amchis. Data were gathered with the help of semi-structured interview and direct observation. The relevant information obtained from informal interview and informal discussions were also noted. Despite some variations in their level of knowledge and skill, all respondent Amchis had the similar pattern of health care practices in the study area. Inspection, interrogation and pulse reading were the most common methods of diagnosis. Use of medicine, Moxibustion and blood-letting were found the most prevalent methods of treatment. Almost all the Amchis had been utilizing traditional tools and instruments for treatment and they had no proper knowledge of sterilization. Decoction, powder, pills and herbal compounds were most common forms of medicines. Medicinal plants and animals were the major sources of medicine. Out of seven VDCs, there were four well established and well functioning THCCs in each four VDCs including medicinal store and library and other two THCCs were also going to be started in these VDCs. Well-trained and experienced Amchis had been employed paying Rs. 10,000 per year to 7,500 per month per head in these THCCs. Some students were under training providing about Rs. 4,000 scholarship per head per month. These THCCs had treated 500 to 1,500 patients last year. All the Amchis and THCCs had been providing health care free cost except by Phoksundo THCC. Home clinic, THCC, door-call visit, out-reach visit and travel pack were some measures adopted by Amchis to provide health care. They used to collect and prepare most of the medicines locally with their own resources. THCCS had been supported by private donors. In addition of treatment and management of illness, they had been providing health education, referral and follow-up services to the patients. The lack of government health care services or other alternatives was not the only factors persuading them for utilization of Amchis health care, but people's high acceptability, high access to this care, easy availability, high coverage, high satisfaction rate, cost free service also were the major contributing factors for utilization of healthcare practices of Amchis. Most of the people had strong faith to Amchis and their treatment and they wanted the promotion of this medical tradition. Almost all Amchis had educated and trained under the lineage-based master-apprentice framework but they had not any recognized degree or certificate. They had been working full time in health care and wanted refresher and skill development training including biomedicine. Each Amchi had possessed 10 to 57 types of medical texts including the fundamental medical treaties rGyud-bZhi (gyu-sheet). Shortage of medicinal ingredients, lack of instruments, lack of finance, and lack of recognition and support by government were some burning problems. Sustainability of THCCs and conservation of their medical tradition were the major challenges faced by Amchis. Establishment of THCCs, exchange of ingredients, formation of DAA and Affiliation in HAA, collection of donation, establishment of medicinal plant nursery, formation of management Committee were some measures adopted by Amchis to overcome the problems and challenges. Considering their contribution to meet local health care needs in the Himalayan communities of Nepal, this medical tradition should be further explored, patronized, promoted and revitalized and should be incorporated into the mainstream of national health care system.